Hospitalizations associated with endemic and non-endemic mosquito-borne arboviruses in Canada, 2002–2023 - Maria Elizabeth Mitri; Antoinette Ludwig; Joanne Tataryn; Salima Gasmi; Mandy Whitlock; Peter A. Buck; Annie-Claude Bourgeois (PLoS ONE, 2026)
Mosquito-borne arboviruses pose a growing public health concern in Canada, particularly in the context of climate change and increased global travel. This study aimed to quantify the burden of endemic and non-endemic mosquito-transmitted arboviral diseases in Canada by examining hospitalization trends from 2002 to 2023. Using administrative hospital data from the Canadian Institute for Health Information (CIHI) and national West Nile virus (WNV) surveillance data, we analyzed patient demographics, temporal and spatial patterns, and disease classification. Hospitalizations were classified as endemic (e.g., WNV) or non-endemic (e.g., dengue, chikungunya, Zika, yellow fever) based on historical presence and vector establishment in Canada. A total of 2,470 unique hospitalizations were identified, with 56.4% attributed to endemic diseases and 39.7% to non-endemic diseases. WNV accounted for over 99% of endemic-related hospitalizations, with peaks in 2003, 2007, and 2012 aligning with national surveillance data. Hospitalizations were highest among males aged 75–79 years, particularly in the southern regions of Saskatchewan, Manitoba, and Ontario. Non-endemic disease hospitalizations, primarily due to dengue and chikungunya, increased after 2010 and were more evenly distributed throughout the year, reflecting travel patterns. Younger adults (20–49 years) were most affected. The study highlights limitations in diagnostic coding and surveillance coverage, particularly the exclusion of Quebec data and underreporting of emerging arboviruses. These findings underscore the utility of hospital administrative data in complementing traditional surveillance systems and identifying populations at risk for severe outcomes. As climate change and travel continue to influence arboviral disease dynamics, integrated data sources are essential for guiding public health planning and response.